The path of ideological and political education in fulfilling the function of psychological nurturing - Xue, Feng; Wei, Naixue; Wu, Xinxiong (Frontiers in Psychology, 2024)
The risk of college students facing psychological problems, such as stress, anxiety, and depression, has increased, which may have a negative impact on their academic performance and overall well-being, especially after the outbreak of the pandemic. This paper summarizes the potential psychological issues that university students may face and the corresponding coping measures. Based on this, a theoretical model of ideological and political education to enhance psychological education was established. There was a total of 446 participants in the study, with a mean age of 21.4 years and 44.6 per cent male. With 406 valid survey responses, the theoretical model was examined using the structural equation modelling method. The results showed that education and teaching, practical activities, counselling services, prevention and intervention, and multi-level platforms are effective measures to protect the psychological health of university students. Based on the insights gained from this study, policies can be implemented to help university students improve their mental health and inspire higher education institutions to prioritize psychological education.